Regulatory approaches to soil contamination and agricultural sustainability - Mohammed Zuhair; Hussain Essam Eldeen Mohammed; Raad Ta’ma Awad Bajjay; Jaafer Kadhem Jasim; Hamza Aljebouri (Environment and Social Psychology, 2025)
Soil contamination poses a serious threat to agricultural sustainability, driven by heavy metals, pesticide residues, nutrient imbalances, and weak governance. Despite extensive research on soil degradation, few studies have systematically integrated scientific diagnostics with regulatory evaluation. This study addresses that gap by combining composite indices—Contaminant Load Index (CLI), Weighted Residue Risk Index (WRRI), Nutrient Deviation Score (NDS), and Adjusted Cation Exchange Capacity (ACE) with a Multi-Criteria Regulatory Score (MCRS) to assess both ecological and institutional dimensions of soil health. Data were collected from ten major agricultural regions, using stratified sampling and validated laboratory methods, and supported by enforcement records. Results reveal that contamination hotspots align with industrial proximity, intensive agrochemical use, and weak regulatory enforcement, while regions with higher MCRS values showed healthier soil indicators. Field validation demonstrated that integrated remediation strategies, combining phytoremediation and organic amendments, significantly reduced contaminant loads and improved fertility, highlighting the feasibility of cost-effective, nature-based solutions. By integrating diagnostics with governance, this study significantly deepens our theoretical understanding of soil sustainability and delivers tangible tools for prioritizing interventions and shaping regulatory frameworks. The results highlight that soil remediation is not solely a technical matter; it is also shaped by ecological and institutional dynamics. Ultimately, the framework proposed here is highly relevant for policymakers aiming to safeguard soil health and bolster agricultural resilience, particularly in regions grappling with similar environmental and governance challenges.